2019
DOI: 10.18393/ejss.533454
|View full text |Cite
|
Sign up to set email alerts
|

Determination of physico-chemical properties and agricultural potentials of soils in Tembaro District, KembataTembaro Zone, Southern Ethiopia

Abstract: The objectives of this study were to classify the soils of Tembaro district, and to identify its potentials for crop production. Five pits representing a pedon each were opened and profile in each pit was described for its morphological, physical and chemical characteristics according to standard procedures. A total of 20 disturbed soil samples and 16 core ring samples were collected from five representative profiles. The samples were analyzed in the laboratory for texture, BD, FC, PWP, Soil pH, EC, OC, TN, av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 18 publications
10
7
0
Order By: Relevance
“…This observation is consistent with findings of Cheng et al. (2016) and Lelago and Buraka (2019) who found that organic carbon is essential for nitrogen availability. It is also consistent with the findings of Ye et al.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is consistent with findings of Cheng et al. (2016) and Lelago and Buraka (2019) who found that organic carbon is essential for nitrogen availability. It is also consistent with the findings of Ye et al.…”
Section: Resultssupporting
confidence: 93%
“…The correlation coefficient (r) for carbon and nitrogen is 0.2 and 0.3 in 0 to 15 and 15 to 30 cm, respectively. This observation is consistent with findings of Cheng et al (2016) and Lelago and Buraka (2019) who found that organic carbon is essential for nitrogen availability. It is also consistent with the findings of Ye et al (2021) who observed a positive correlation between soil nitrogen and soil carbon.…”
Section: Organic Carbon (%Oc)supporting
confidence: 93%
“…The analyzed soil parameters included soil texture, soil pH, total organic carbon, total nitrogen (N), available phosphorus (P), exchangeable bases, and cation exchange capacity (CEC). Standard analytical methods as outlined by Lelago and Buraka (2019) were employed for the soil analysis.…”
Section: Soils Datamentioning
confidence: 99%
“…The tropical rainforest of Malaysia is one of the most luxuriant and complex habitats in the world, which preserves the wealth of flora and fauna [39]. Notwithstanding the spectral features of forestland in Malaysia, many forest areas have been converted for urban and industrial settlement purposes and agricultural production [40,41]. Reportedly, the rehabilitation processes of degraded forests in the tropical regions of Malaysia, especially in Peninsular Malaysia, have been successfully applied with the plantation of A. mangium [35,42], Azadirachta excelsa, Pinus caribaea, and Khaya ivorensis [2].…”
Section: Introductionmentioning
confidence: 99%